Encapsulation of vortioxetine with cyclodextrins via host–guest inclusion complex: Synthesis, characterization, solubility, and in vitro dissolution studies. Issue 4 (21st March 2023) - Inam, Muhammad; Phan, Chi Uyen; Wang, Jian‐Wei; Jamshed, Muhammad; Hu, Xiurong; Tang, Guping
Abstract: Drug solubility plays a significant role in the development of drug formulation. The objectives of this work are to improve the solubility and dissolution rate of vortioxetine (VT) by preparing its inclusion complexes (ICs) with β‐Cyclodextrin (β‐CD) and γ‐Cyclodextrin (γ‐CD). The ICs were prepared in 1:1 M ratio via recrystallization method and characterized by P‐XRD, FT‐IR, 1 H NMR, 2D NOESY, and DSC. Further, the crystal structure of VT‐β‐CD was analyzed by SC‐XRD. P‐XRD data obtained for ICs describe the crystalline pattern. The DSC analysis shows change in the thermal behavior of VT, CDs and ICs. FT‐IR analysis shows shifting of frequencies in ICs when compared with the pristine VT drug and CDs. The 2D NOESY in DMSO‐d 6 indicates weak interaction between the VT and CD molecules. The crystal structure of VT‐β‐CD consists of one guest VT, one host CD, and nine water molecules in the crystal lattice. The solubility of ICs was significantly improved in distilled water, pH 1.2 acidic, and phosphate buffer pH 6.8 medium, as compared with the solubility of the pristine VT drug. The in vitro dissolution rate of ICs in different dissolution media was investigated, which was higher than that of the commercial product of VT. Abstract : The objectives of this work are to improve the solubility and dissolution rate of vortioxetine (VT) by preparing its inclusion complexes (ICs). The ICs were prepared through recrystallization method and characterized by P‐XRD, FT‐IR, 1 H NMR, 2D NOESY, and DSC. The crystal structure of VT‐β‐CD was analyzed by SC‐XRD. Inclusion complexes (ICs) demonstrated higher solubility and dissolution rate compared with pristine VT.